Hybrids: on the crime–terror nexus - Ruggiero, Vincenzo (International journal of comparative and applied criminal justice, 2019)
Terrorist organisations may complement their military capability with functioning infrastructures and profitable activity in economic ventures as well as in crime. This leads many commentators to focus on the increasing overlap between terrorism and crime, including and particularly organised crime. The present paper is devoted to the analysis of this controversial overlap, and after providing a concise outline of definitions of organised crime and terrorism found in criminology, highlights similarities and differences between the two forms of criminality, along with the ambiguity of the very notion of “crime-terror nexus.”